Diálogos intertextuais no feminino: Margaret Drabble - Siqueira, Ramira Maria [UNESP]; Pires, Silva [UNESP] (My University, 2004)
In The Middle Ground (1980), Margaret Drabble uses an intertextual web to depict the feminine search for identity and psychological integrity in middle age. This paper attempts to identify and analyze the absorption and integration of other texts in The Middle Ground. The dialogue, both in theme and style, with Virginia Woolf's Mrs Dalloway is initially considered, mostly from the perspective of parody. Other confluences are also studied: with Russian fairy tales, with paintings by Hans Holbein, J. B.Vanmour, Van Dyck, Claude Lorrain and Peter de Hooch, and also its references to the whole of Drabble's literary work.

Em The Middle Ground, de 1980, Margaret Drabble amplifica sua voz feminina em busca da identidade e da coerência psicológica, por meio de uma teia de diálogos e relações intertextuais. Enfocamos, neste trabalho, inicialmente, o percurso, evidenciado pela própria escritora, de seu descobrimento da obra de Virginia Woolf. Em seguida, identificamos, em The Middle Ground, a presença de Woolf, tanto por meio de algumas confluências de estilo, quanto por meio de intertexto paródico com Mrs Dalloway, publicado em 1925, de Virginia Woolf. Na seqüência, abordamos outros diálogos de Drabble, no romance em questão, com sua própria obra, com contos de fada e, também, com pinturas dos séculos XVI e XVII de Hans Holbein, J.B.Vanmour, Van Dyck, Claude Lorrain e Peter de Hooch.
Female intertextual dialogues: Margaret Drabble
Keywords: Intertextuality; Margaret Drabble; Parody; The Middle Ground; Womens literature